2018
DOI: 10.1038/s41598-018-34973-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivated stallion spermatozoa fail to exhibit a rheotaxis-like behaviour, unlike other species

Abstract: The journey of spermatozoa through the female genital tract is facilitated by rheotaxis, or the cell’s preference to swim against a flow, as well as thigmotaxis, the wall tracking behaviour, which guides them to the site of fertilisation. The aim of this study was to characterise the rheotactic and thigmotactic response of stallion sperm within a microfluidic channel. Stallion sperm rheotaxis was assessed within the microfluidic channel with regard to: (i) A range of flow velocities, (ii) Varying media viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Miki and Clapham (2013) proved for the first time that both human and mice spermatozoa orientate their swimming against a fluid flow, process known as rheotaxis. Latter, El-Sherry et al (2014) and Romero-Aguirregomezcorta et al (2018) confirmed the occurrence of this phenomenon also in bovine, stallion, and ram spermatozoa, suggesting rheotaxis as a conserved feature of mammalian spermatozoa. Furthermore, the existence in mice of oviductal flow toward the uterus intensified after copula supports rheotaxis as a long-distance guidance mechanism within the oviduct (Miki and Clapham, 2013).…”
Section: Sperm Selection Based On Guidance Mechanismssupporting
confidence: 55%
“…Miki and Clapham (2013) proved for the first time that both human and mice spermatozoa orientate their swimming against a fluid flow, process known as rheotaxis. Latter, El-Sherry et al (2014) and Romero-Aguirregomezcorta et al (2018) confirmed the occurrence of this phenomenon also in bovine, stallion, and ram spermatozoa, suggesting rheotaxis as a conserved feature of mammalian spermatozoa. Furthermore, the existence in mice of oviductal flow toward the uterus intensified after copula supports rheotaxis as a long-distance guidance mechanism within the oviduct (Miki and Clapham, 2013).…”
Section: Sperm Selection Based On Guidance Mechanismssupporting
confidence: 55%
“…However, while PTP in the equine spermatozoon flagellum is elevated under different capacitating conditions in vitro, so far all attempts to establish its relationship with hyperactive motility have had limited success [ 12 ]. Romero-Aguirregomezcorta [ 13 ] showed that the type of hyperactivated motion induced in vitro by species-specific hyperactivation agonists significantly differed in stallion in relation to human or ram spermatozoa, and led to the absence of a rheotactic response in stallion sperm. As an explanation, the authors suggested a different role of sperm hyperactivation in the horse.…”
Section: Introductionmentioning
confidence: 99%
“…6, [49] 4 [50] and 5.9 MPa s( Figure S3), respectively.D ifferent from the motion in sperm media (ca. 0.9 MPa s), [51] the viscoelasticity and cell composition of such biological fluids lead to adrifting behavior of the microcarrier during motion, which is only observed when the micromotor swims close to as urface.M C3 swam efficiently in saliva at 171 AE 41 mms À1 (Figure 2ai and Video S7) while being magnetically guided to avoid big squamous cells. [52] After 10 min, the microcarrier was found with mucus (mainly consisting of mucopolysaccharides and glycoproteins) [53] as well as some small cells attached on its surface,d isturbing its steering capability.Inblood, the microcarriers showed amore intricate swimming behavior due to the complex blood composition…”
Section: Resultsmentioning
confidence: 99%